Effects of Teacher’s error corrections on students’ attitude towards English Class in the Intermediate Intensive English I, at The Department of Foreign Languages of the University of El Salvador, in the Semester II – 2010 - Liévano Avilés, Carlos Rodolfo; Marroquín Hernández, Karmina Estela; Santana Olmedo, Analía Beatriz (2024)
Both students’ errors and teacher’s error corrections is a common phenomenon observed in daily classroom activities in the teaching-learning process. It is studied in the present research paper, with particular attention paid to teacher’s usual practice on error corrections and its relationship with students’ attitude. The present research paper is done with the purpose of finding the effects of teacher’s error corrections on students ‘attitude towards English class in the Intermediate Intensive English I, at the Department of Foreign Languages of the University of El Salvador, in the semester II-2010because is well known that teachers and students share such common views as the importance of error corrections and the types of errors that need to be corrected. Therefore, errors are often a sign of learning in language acquisition process. However, there exists a considerable discrepancy as to the techniques of error corrections. For instance, students do not favor the overall correction, though practiced by most teachers. Such a controversy requires teachers to make as many and possible improvements as they can about their current error corrections practice. Thus, to reach the purpose stated above, the research process followed a structured pattern containing the following terms: the conceptual framework, which describes important aspects and theories related to teacher’s error corrections on students while learning English, the methodology that contains the methods, the sample and the way how data analysis is done. Then, there is found focus group and class observation findings, where students stated that they like to be corrected by the teacher in the moment they make an error, but what they really like the most or they really care the most is the way how their teacher corrects the errors.